English An implementation of smart agriculture for optimizing growth using sonic bloom and IoT integrated - Mia Galina; Cutifa Safitri; Iksan Bukhori; Arthur Silitonga; Antonius Suhartomo (JURNAL INFOTEL, 2022)
This paper proposes the implementation of IoT-based agriculture monitoring with audio growth (sonic bloom) to optimize the growth of plants and harvest. Sonic bloom is a technology that combines high-frequency sound waves from living things, nature or music, and organic nutrients, which aims to make plants grow more optimally so that they can increase productivity. The method’s main advantage is implementing an innovative IoT monitoring hybrid with audio growth systems to boost the plantation growth and maximize the yield. Our experiment in 10 planters using chilies, has proven the proposed procedure. This work is backed up with literature studies of the audio growth (sonic bloom) in IoT technologies. To validate our findings, four parameters were measured through different sensors such as light sensors, temperature, humidity, and soil moisture. It was found that the proposed method can achieve significant results against the comparison in terms of plant heights and new sprouts for the harvest.